Differences in the individual curative effect of acupuncture for obese women with polycystic ovary syndrome based on metagenomic analysis: study protocol for a randomized controlled trial - Fan, Huaying; Hong, Xiaojuan; Zeng, Jiuzhi; Wang, Xue; Chen, Jiao (Current controlled trials in cardiovascular medicine, 2021)
Background Polycystic ovary syndrome is a common cause of infertility and shows a high incidence in women of reproductive age. Acupuncture is an appropriate adjunctive treatment for PCOS. However, the add-on effect of acupuncture as an adjunctive treatment for obese women with PCOS has not been studied, and previous studies indicate that there are individual differences in the curative effect of acupuncture, while deeper research on the mechanism of differences in the individual curative effect of acupuncture for obese women with PCOS is still lacking. This trial aims to assess the add-on treatment efficacy of acupuncture for obese women with PCOS and to explore the role of the gut microbiome on the differences in the individual curative effect of acupuncture based on metagenomic analysis. Methods/design This is an open-label, randomized, controlled trial. A total of 86 obese women with PCOS will be recruited. Subjects will be randomly assigned to a study group and a control group in a 1:1 ratio, with 43 subjects in each group (10 patients from each group who meet the study criteria will participate in the metagenomic analysis). An additional 10 subjects who meet the study criteria will be recruited to a healthy control group. The study group will receive acupuncture and clomiphene citrate treatment; the control group will only receive clomiphene citrate. Acupuncture treatment will be conducted three times a week from the fifth day of menstruation or withdrawal bleeding until the start of the next menstruation, for up to three menstrual cycles. The primary outcome will be LH/FSH. The secondary outcomes will comprise biometric features, hormone biomarkers, metabolic biomarkers, inflammatory biomarkers, Self-Rating Anxiety Scale, Self-Rating Depression Scale, and metagenomic analysis. The outcomes will be measured at baseline and post-intervention. Data will be analyzed using SPSS 19.0, and the gut microbiome will be analyzed using metagenomic analysis. Discussion In this study, we are evaluating the add-on effects of acupuncture and exploring the mechanism of the differences in the individual curative effect of acupuncture based on the gut microbiome, which may provide evidence to explain the different outcomes of different trials on acupuncture for PCOS and hopefully to provide a new aspect to study the mechanism of acupuncture’s treatment effect. Trial registration Chinese Clinical Trial Registry ChiCTR2000029882 . Registered on 16 February 2020